Prosthodontic Rehabilitation for Edentulous Patients With Palatal Defect: Report of Two Cases - Fen-Huey Lin; Tsung-Chih Wang (Journal of the Formosan Medical Association, 2011)
Cancer resection is the most common cause of acquired palatal defects, whereas cleft palate is the main cause of congenital defects. Palatal defect can be repaired by reconstructive surgery and/or a dental prosthesis. We present prosthodontic rehabilitation of two maxillary edentulous patients, one with a surgically induced palatal defect and the other with congenital cleft palate. In case 1, an 86-year-old man underwent surgical removal of soft-palate squamous cell carcinoma. The acquired palatal defect was repaired by a maxillary complete denture with a posteriorly extended speech bulb. The final prostheses provided good chewing and speech functions. In case 2, a congenital cleft palate in a 65-year-old man was repaired by a maxillary complete denture with superior extension of the obturator, which was designed to improve retention and stability of the upper single denture. He was satisfied with the upper denture after prosthesis placement. Conventional maxillary complete denture with a posteriorly extended speech bulb or modified obturator provides a good chance to restore oral functions in patients with palatal defects. The patients' skill and previous experience of denture wearing might have been important in their successful treatment. However, different patients present with unique problems and need to be treated individually.